Equilibrium viscosity and structural change in the Cu47.5Zr45.1Al7.4 bulk glass-forming liquid. (1st February 2020) - Jiang, Hao-Ran; Bochtler, Benedikt; Frey, Maximilian; Liu, Qi; Wei, Xian-Shun; Min, Yang; Riegler, Sascha S.; Liang, Dan-Dan; Busch, Ralf; Shen, Jun
Abstract: The low temperature viscosities of Cu47.5 Zr45.1 Al7.4 glass-forming liquid are measured by thermomechanical analysis in three-point beam bending mode. The experimental equilibrium values are fitted with the Vogel-Fulcher-Tammann (VFT) function, and the fragility parameter of the supercooled liquid is determined to be D * = 20.6. Viscosity measurements during isothermal annealing at 710 K show an initial relaxation from the glassy state into the supercooled liquid, followed by an anomalous viscosity increase of about two orders of magnitude. In-situ transmission electron microscope (TEM) and spherical aberration-corrected TEM investigations reveal that the effects of primary crystallization, nanoscale decomposition and structural ordering might be responsible for the anomalous viscosity behavior. The change in dynamic properties of the supercooled liquid, which is reflected by the larger VFT fitting parameter D * = 41.9 of the new annealed state reached before the final crystallization, is suggested to be not only related to the nanoscale structure change, but may also be caused by the change in chemical composition of the new annealed glass due to the primary crystallization. Furthermore, possible mechanisms for the nanoscale phase separation and the formation of atomic clusters are discussed based on the results of high-resolution TEM experiments. Graphical abstract: Image, graphical abstract